The hunchback's tailor : Giovanni Giolitti and liberal Italy from the challenge of mass politics to the rise of fascism, 1882-1922 - De Grand, Alexander J., 1938- (Italian and Italian American studies., 2001)
This work examines the political life of Italy's most notable prime minister after Cavour. Alongside Georges Clemenceau and David Lloyd George, Giovanni Giolitti (1842-1928) stands out as one of the major liberal reformers of late 19th- and early 20th-century Europe.